Sweet potato (Impomoea Batatas) flour production using solar radiation under plastic house - Hasmizie Hassan (2011)
This research help us to understand more on the drying method using the solar radiation under plastic house and compare it performance with oven drying method in order to dried sweet potato. There three types of variety of sweet potato used in the researched that were Jepun variety, vitato variety and Madu variety. The samples were dried using both method and the result was analyzed to gained the significant information. Furthermore, the research was to evaluate the significant parameter that influence the drying rate, moisture content reading, and the performance of these two methods in drying the sweet potato for flour production. Drying method is one of the crucial steps in flour production which the quality of the flour depend on the drying method. In drying technique using solar radiation, the sample thickness, temperature, and sweet potato variety are the main parameter focus in the research. We are evaluating the drying rate to identify how much time it needed to reach the suitable moisture content for flour production that is 8% where this rate is the best moisture content for good quality flour production depending on the sample thickness, variety and temperature. At the end, the characteristic of solar drying under the plastic house was identified. For solar drying method, it be done at UMK Agro Park and for oven drying method it be done at UMK FASA's laboratory.